2008 First International Conference on Infrastructure Systems and Services: Building Networks for a Brighter Future (INFRA) 2008
DOI: 10.1109/infra.2008.5439650
|View full text |Cite
|
Sign up to set email alerts
|

Cost overruns in large-scale transportation infrastructure projects: Which explanations can be given?

Abstract: Managing large-scale transportation infrastructure projects is difficult due to frequent misinformation about the costs which results in large cost overruns that often threaten the overall project viability. This paper investigates the explanations for cost overruns that are given in the literature. Overall, four categories of explanations can be distinguished: technical, economic, psychological, and political. Political explanations have been seen to be the most dominant explanations for cost overruns. Agency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
152
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(160 citation statements)
references
References 26 publications
(28 reference statements)
3
152
0
5
Order By: Relevance
“…Relative: although not explicit in the definition, cost overruns are calculated as a percentage of the estimated costs C refers to the "the actual final costs" refers to the "estimate made at the fullfunds authorization" (Cantarelli et al 2010) Cost overruns is calculated as "Actual outturn costs minus estimated costs as a percentage of estimated costs"…”
Section: Definition Of Cost Overrunsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative: although not explicit in the definition, cost overruns are calculated as a percentage of the estimated costs C refers to the "the actual final costs" refers to the "estimate made at the fullfunds authorization" (Cantarelli et al 2010) Cost overruns is calculated as "Actual outturn costs minus estimated costs as a percentage of estimated costs"…”
Section: Definition Of Cost Overrunsmentioning
confidence: 99%
“…Assessment of cost overruns in the literature Nevertheless, especially for long projects in the public sector, it is likely that multiple changes occur over time (Flyvbjerg et al 2002), which affects the definition of "original estimates". Cantarelli et al (2010, p.4), quoting (Cantarelli et al 2009), highlight that "the estimated costs at the real decision to build are usually lower than those at later stages of the decision-making process", which is a situation called "lock-in", and that "references to the formal decision to build do not always provide an accurate picture of cost overruns" (Cantarelli et al 2010). Merrow (2011, p.38) defines as the "estimate made at the full-funds authorization", and suggests to evaluate cost overruns through (i) a systematic collection of a large number of cases, (ii) the calculation of cost overruns of single projects, and (iii) the definition of a threshold (25%) to determine the actual cost overruns.…”
Section: Definition Of Cost Overrunsmentioning
confidence: 99%
“…Authors such as Martin et al (2006), EC Harris and TRL (2009), Flyvbjerg et al (2008), HS2 (2009, NAO (2012), Cantarelli et al (2010Cantarelli et al ( , 2012, Helm (2013) Madter and Bower (2015) and HM Treasury (2010 point toward increasing client and management costs, as well as a lack of skills and ability within ICOs. Indeed, the Infrastructure Cost Review (ICR) (HM Treasury, 2010) identified client leadership, overly complicated procurement practices and poor design specification as the top three areas for reducing costs.…”
Section: Infrastructure Client Organisationsmentioning
confidence: 99%
“…Other measures proposed recently includes reference class forecasting and public sector accountability (Flyvbjerg 2007(Flyvbjerg , 2008Berechman and Chen, 2011;Cantarelli et al,2012cited in Lind, & Brunes, 2014. The reference class forecasting uses the actual performance in a reference class to project accuracy by identifying relevant reference class of past and similar projects, establishing a probability distribution for the identified reference class and comparing the specific project with the reference class distribution to establish the likely outcome of the project.…”
Section: Mitigating Measures For Cost Overrunmentioning
confidence: 99%